Análisis del principio de precaución en Derecho internacional público: perspectiva universal y perspectiva regional europea - Jiménez de Parga y Maseda, Patricia (Política y Sociedad, 2003)
This article analyses the precautionary principIe from the perspective of Public International Law, and, more specifically, following International Environmental Law.The first section centers upon three topics the definition of the main elements of the principle its status in international law and the distinction between precaution and prevention. The second section focuses an Community law and tries to assert if the European Union has contributed to a definition of the precautionary Principle as well as it documents its expansion into other areas.